Running a bar for dummies - Foley, Ray; Dismore, Heather (New Jersey : John Wiley & Son, Inc., 2014)
Running a Bar For Dummies, 2nd Edition shows established and future bar owners how to establish and maintain a successful business. Using clear, concise language, this For Dummies guide contains all the information you need to start your bar off on the right foot. From grand opening to last call, you'll discover the insider tricks that keep the business end running smoothly and the customers happily engaged. With updated information on marketing and social media, the book walks you step by step through the entire process, revealing the nitty-gritty details most new bar owners only discover after starting. The bar business continues to grow; however, securing running capital and having knowledge about the business are cited as the two biggest reasons new bars fail. Running a Bar For Dummies, 2nd Edition shines a light on these issues to help bar owners prepare properly. The book helps you find your way through the maze of licensing and permits, developing a business plan, and preparing for your grand opening, plus offers clear, no-nonsense guidance on dealing with tough customers. Every step of the way, Running a Bar For Dummies, 2nd Edition is a reference you can count on.
1. Cheers! Getting started in the bar industry -- 2. Gearing up to open the doors -- 3. Employees, customers, and products : managing the " right stuff " -- 4. Managing your inventory, revenue, and future -- 5. The part of tens
Includes index.
Keywords: BARS (DRINKING ESTABLISHMENTS) -- MANAGEMENT